Synthesis, characterization and catalytic application of Ru-II-ethylenediamine complex - mesoporous silica as heterogeneous catalyst system in chemo-selective hydrogenation of alpha,beta-unsaturated carbonyl compounds - Ghosh, Anirban; Kumar, R (Microporous and Mesoporous Materials, 2005)
An efficient heterogeneous catalyst system for chemo-selective hydrogenation of alpha,beta-unsaturated aldehydes was synthesized, involving anchoring of a Ru-II-phosphine complex on the inner surfaces of organo-functionalized (propylamine and propylethylenediamine) mesoporous MCM-41 and MCM-48 materials. Powder XRD, SEM and TEM experiments reveal highly ordered hexagonal and cubic patterns of the organically modified MCM-41 and MCM-48 materials, respectively, even after incorporation of Ru complexes. Moreover, the integrity of the Ru complex was retained after anchoring into the mesoporous hosts, which was supported by FTIR, P-31 CP MAS NMR and XPS analyses. This heterogeneous catalyst shows promising activity and chemo-selectivity towards hydrogenation of carbonyl groups in alpha,beta-unsaturated aldehydes. The effects of reaction temperature, reaction time and hydrogen pressure on the activity and selectivity were studied in detail. The anchored solid catalysts can be recycled effectively and reused several times without any loss in activity and selectivity. Although, the initial activity of the same Ru complex when grafted onto the organically modified surfaces of fumed silica is comparable to corresponding MCM41/MCM-48 catalysts, the activity and chemo-selectivity significantly decrease during recycle of the catalyst due to leaching. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: chemo-selective; heterogeneous catalysis; Heterogenization; Hydrogenation; mesoporous materials; organo-functionalization; Ru-II-ethylenediamine complex; unsaturated aldehyde

Eco-friendly synthesis of epichlorohydrin catalyzed by titanium silicate (TS-1) molecular sieve and hydrogen peroxide - Pandey, Rajesh Kumar; Kumar, Rajiv (Catalysis Communications, 2007)
In a mixed solvent system of acetonitrile and methanol, titanium silicate molecular sieve, TS-1, having MFI topology, efficiently catalyses the epoxidation of allyl chloride to the corresponding epichlorohydrin in excellent yields using dilute hydrogen peroxide (45%) as an oxidizing agent. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: allyl chloride; epichlorohydrin; epoxidation; heterogeneous catalysis; selectivity; titanium silicalite-1

Cellulose conversion under heterogeneous catalysis - Dhepe, Paresh Laxmikant; Fukuoka, Atsushi (ChemSusChem, 2008)
In view of current problems such as global warming, high oil prices, food crisis, stricter environmental laws, and other geopolitical scenarios surrounding the use of fossil feedstocks and edible resources, the efficient conversion of cellulose, a non-food biomass, into energy, fuels, and chemicals has received much attention. The application of heterogeneous catalysis could allow researchers to develop environmentally benign processes that lead to selective formation of value-added products from cellulose under relatively mild conditions. This Minireview gives insight into the importance of biomass utilization, the current status of cellulose conversion, and further transformation of the primary products obtained
Keywords: Biomass; cellulose; heterogeneous catalysis; supported catalysts

Energy-efficient syngas production through, catalytic oxy-methane reforming reactions - Choudhary, Tushar V.; Choudhary, Vasant R. (Angewandte Chemie-International Edition, 2008)
Keywords: fuels; heterogeneous catalysis; methane activation; Partial oxidation; Syngas

Feasibility studies and dynamics of catalytic liquid phase esterification reactions in a micro plant - Kulkarni, A. A.; Zeyer, K. -P.; Jacobs, T.; Kaspereit, M.; Kienle, Achim (Chemical Engineering Journal, 2008)
We present a new micro reactor concept which is suitable for investigations of heterogeneously catalyzed liquid phase reactions. In the set-up two reactants are mixed in a commercially available interdigital micro mixer. The outlet of the micro mixer is connected to a modular micro reactor that consists of stacked plates. Each plate contains a milled meandering channel filled with catalyst beads. By using a variable number of plates the residence time can be manipulated and thus adjusted for a specific task. The synthesis of butyl acetate is considered as a model reaction since it has been investigated in detail in conventional reaction systems. In a first step, some experimental results of the heterogeneously catalyzed reaction are presented. In the second part, the set-up is operated as a chromatographic reactor. Dynamic behaviour is investigated applying the frontal analysis mode and the elution chromatography mode. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: chromatographic reactor; heterogeneous catalysis; integrated process; modular micro reactor

Electronic decoupling of surface layers from bulk and its influence in oxidation catalysis: a molecular beam study - Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan; Gopinath, Chinnakonda S. (Applied Surface Science, 2009)
Interactions between oxygen and Pd-surfaces have important implications, especially towards oxidation reactions, and influence of subsurface oxygen to oxidation reactions is the focus of the present study. In our efforts to understand the above aspects, CO oxidation reactions have been carried out with mixed molecular beam (MB), consisting CO and O(2), on Pd(1 1 1) surfaces under a wide variety of conditions (T = 400-900 K, CO: O(2) = 7: 1 to 1: 10). A new aspect of the above reaction observed in the transient kinetics regime is the evidence for oxygen diffusion into Pd subsurface layers, and its significant influence towards CO oxidation at high temperatures (>= 600 K). Interesting information derived from the above studies is the necessity to fill up the subsurface layers with oxygen atoms to a threshold coverage (theta(O-sub)), above which the reactive CO adsorption occurs on the surface and simultaneous CO(2) production begins. There is also a significant time delay (G) observed between the onset of oxygen adsorption and CO adsorption (and CO(2) production). Above studies suggest an electronic decoupling of oxygen covered surface and subsurface layers, which is slightly oxidized, from the metallic bulk, which induces CO adsorption at high temperatures and simultaneous oxidation to CO(2). (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic decoupling; heterogeneous catalysis; molecular beam; Oxidation; Pd(111); Subsurface diffusion

Recyclable amberlyst-70 as a catalyst for biginelli reaction: an efficient one-pot green protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones - Chandak, Hemant S.; Lad, Nitin P.; Upare, Pravin P. (Catalysis Letters, 2009)
An environmentally benign aqueous protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones using Amberlyst-70 as a recyclable catalyst has been developed. The use of resinous, nontoxic, thermally stable and inexpensive Amberlyst-70, as a recyclable heterogeneous catalyst, makes the process simple with negligible chemical waste. Thus renders this method an environmentally acceptable synthetic tool for Biginelli reaction.
Keywords: Amberlyst-70; Biginelli reaction; green chemistry; heterogeneous catalysis

Synthesis, characterization and catalytic performance of Sn-MCM-48 in solvent-free Mukaiyama-type aldol condensation reactions - Taralkar, U. S.; Kalita, Pranjal; Kumar, Rajiv; Joshi, P. N. (Applied Catalysis A-General, 2009)
The influence of various synthesis variables on the physico-chemical properties of mesoporous stannosilicate molecular sieves with MCM-48 structure (Sn-MCM-48) has been investigated. Sn-MCM48 has been used as a new heterogeneous catalyst in solvent-free Mukaiyama-type aldol reactions. Invariably, the beta-hydroxy ester selectivity was found to be 100% irrespective of the conversion level. The product yield was found to increase, to reach a maximum (70%), and then to decrease with the increase in tin content. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Characterization; heterogeneous catalysis; Hydrothermal synthesis; Mesoporous molecular sieves; Mukaiyama-aldol condensation; Sn-MCM-48

Covalently immobilized triphenylphosphine rhodium complex: synthesis, characterization, and application in catalytic olefin hydrogenation - Wang, Lei; Jia, Mingjun; Shylesh, Sankaranarayanapillai; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Singh, Anand Pal; Thiel, Werner R. (Chemcatchem, 2010)
A trimethoxysilane functionalized triphenylphosphine was coordinated to rhodium(I) and the resulting rhodium complex was covalently bound to a mesoporous SBA-15 support. The catalytic activity of this hybrid material was studied for the hydrogenation of 2-cyclohexen-1-one and compared with the corresponding homogeneous catalyst. According to the (31)P-MAS NMR data, the catalytically active species was stable against oxidation; no structural change could be detected after exposing it to air for more than two months. Transmission electron microscopy (TEM) measurements on the used catalyst confirmed that the rhodium species was also stable against reduction to the metal because the formation of rhodium nanoparticles during the catalysis could be excluded. The kinetic curves of the recycled system confirmed that this hybrid catalyst shows excellent activity, selectivity, stability, and reusability, and is truly heterogeneous in the hydrogenation reaction.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; mesoporous materials; Rhodium

Heterogenized copper catalysts for the amination of arylhalide: synthesis, characterization and catalytic applications - Patil, Nandkumar M.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Applied Catalysis A-General, 2010)
This research investigated the synthesis, characterization and catalytic activity of heterogenized copper complexes for the selective amination of aryl halides. Amination reactions using homogeneous copper catalyst systems are not generally selective and it is also difficult to recover the catalyst from the homogeneous system for recycling. To overcome these difficulties, our efforts were directed towards the development of cheaper heterogeneous catalyst systems, which can be easily recovered and recycled. Heterogenized analogs of the homogenous Cu complexes were prepared using two methods: (a) encapsulation of copper complexes in zeolite-Y and (b) tethering of copper complexes on various supports like zeolite-Y, silica, charcoal, or clay. The encapsulated and tethered copper catalysts on zeolite-Y were characterized using EPR, Diffused reflectance UV-vis, XRD, IAS, ICPES, SEM, and TEM. The results confirmed that the copper complexes were truly heterogenized in zeolite-Y support. Encapsulated and tethered copper complexes were tested for amination of aryl iodide. The effects of various reaction parameters were examined using tethered Cu(Phen)(PPh(3))Br-PTA-Y catalyst to determine optimum conditions. A recycle study of encapsulated and tethered Cu catalyst was carried out to test their robustness for possible commercial exploitation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Amination; C-N coupling; Copper; heterogeneous catalysis; mesoporous materials

Renewable H-2 from glycerol steam reforming: effect of La2O3 and CeO2 addition to Pt/Al2O3 catalysts. - Montini, Tiziano; Singh, Rakesh; Das, Piyali; Lorenzut, Barbara; Bertero, Nicolas; Riello, Pietro; Benedetti, Alvise; Giambastiani, Giuliano; Bianchini, Claudio; Zinoviev, Sergey; Miertus, Stanislav; Fornasiero, Paolo (Chemsuschem, 2010)
Glycerol is the main byproduct of biodiesel production and its increased production volume derives from the increasing demand for biofuels. The conversion of glycerol to hydrogen-rich mixtures presents an attractive route towards sustainable biodiesel production. Here we explored the use of Pt/Al2O3-based catalysts for the catalytic steam reforming of glycerol, evidencing the influence of La2O3 and CeO2 doping on the catalyst activity and selectivity. The addition of the latter metal oxides to a Pt/Al2O3 catalyst is found to significantly improve the glycerol steam reforming, with high H-2 and CO2 selectivities. A good catalytic stability is achieved for the Pt/La2O3/Al2O3 system working at 350 degrees C, while the Pt/CeO2/Al2O3 catalyst sharply deactivates after 20 h under similar conditions. Studies carried out on fresh and exhausted catalysts reveal that both systems maintain high surface areas and high Pt dispersions. Therefore, the observed catalyst deactivation can be attributed to coke deposition on the active sites throughout the catalytic process and only marginally to Pt nanoparticle sintering. This work suggests that an appropriate support composition is mandatory for preparing high-performance Pt-based catalysts for the sustainable conversion of glycerol into syngas.
Keywords: biofuels; Glycerol; heterogeneous catalysis; platinum; supported catalysts

Transesterification of cyclic carbonates to dimethyl carbonate using solid oxide catalyst at ambient conditions: environmentally benign synthesis - Sankar, Meenakshisundaram; Satav, Srikanth; Manikandan, Palanichamy (Chemsuschem, 2010)
Keywords: calcium; environmental chemistry; heterogeneous catalysis; transesterification zinc

One-Pot method for the selective conversion of hemicellulose from crop waste into C5 sugars and furfural by using solid acid catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Chemsuschem, 2012)
We present a solid-acid catalyzed one-pot method for the selective conversion of solid hemicellulose without its separation from other lignocellulosic components, such as cellulose and lignin. The reactions were carried out in aqueous and biphasic media to yield xylose, arabinose, and furfural. To overcome the drawbacks posed by mineral acid methods in converting hemicelllulose, we used heterogeneous catalysts that work at neutral pH. In a batch reactor, these heterogeneous catalysts, such as solid acids (zeolites, clays, metal oxides etc.), resulted in >90% conversion of hemicellulose. It has been shown that the selectivity for the products can be tuned by changing the reaction conditions, for example, a reaction carried out in water at 170 degrees C for 1 h with HBeta (Si/Al=19) and HUSY (Si/Al=15) catalysts gave yields of 62 and 56% for xylose and arabinose, respectively. With increased reaction time (6 h) and in presence of only water, HUSY resulted in yields of 30% xylose+arabinose and 18% furfural. However, in a biphasic reaction system (water+p-xylene, 170 degrees C, 6 h) yields of 56% furfural with 17% xylose+arabinose could be achieved. It was shown that with the addition of organic solvent the furfural yield could be increased from 18 to 56%. Under optimized reaction conditions, >90% carbon balance was observed. The study revealed that catalysts were recyclable with a 20% drop in activity for each subsequent run. It was observed that temperature, pressure, reaction time, substrate to catalyst ratio, solvent, and so forth had an effect on product formation. The catalysts were characterized by means of X-ray diffraction, temperature-programmed desorption of NH3, inductively coupled plasma spectroscopy, elemental analysis, and solid-state NMR (Si-29, Al-27) spectroscopy techniques.
Keywords: analytical methods; Biomass; carbohydrates; heterogeneous catalysis; zeolites

One-pot sol-gel preparation for efficient cobalt-molybdenum-titania hydrotreating catalysts - Nguyen, D. L.; Gillot, S.; Souza, D. O.; Blanchard, P.; Lamonier, Carole; Berrier, E.; Kotbagi, T. V.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Cristol, S.; Payen, E.; Lancelot, Christine (Chemcatchem, 2012)
Titania-based hydrodesulfurization catalysts were prepared by using a one-pot solgel method with the titanium peroxo complex as titanium precursor and molybdenum and cobalt precursors dissolved in the aqueous hydrogen peroxide solution used during synthesis. Catalysts with MoO3 loadings varying from 5 to 40 wt?% and a Co/Mo atomic ratio of 0.5 were prepared. Solids with molybdenum loadings below 20 wt?% MoO3 demonstrated poor hydrodesulfurization activity for the model compound thiophene. This was attributed to the presence of a large amount of embedded cobalt and molybdenum species in the titania matrix. A significant increase in the catalytic activity was observed for solids containing 20 and 25 wt?% of MoO3 on which active species appeared to be accessible on the titania surface. Furthermore, the highest conversion obtained on these solgel solids was superior to the highest conversion obtained on reference catalysts prepared through the impregnation of ammonium heptamolybdate and cobalt nitrate on commercial titania.
Keywords: cobalt; heterogeneous catalysis; Molybdenum; sol-gel process; titanium

Transesterification of diethyl oxalate with phenol over sol-gel MoO3/TiO2 catalysts - Kotbagi, Trupti; Duy Luan Nguyen; Lancelot, Christine; Lamonier, Carole; Thavornprasert, Kaew-Arpha; Zhu Wenli; Capron, Mickael; Jalowiecki-Duhamel, Louise; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck (Chemsuschem, 2012)
The transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in the liquid phase over very efficient MoO3/TiO2 solid-acid solgel catalysts. A selectivity of 100?% with a remarkable maximum yield of 88?% were obtained, which opens the route to downstream phosgene-free processes for the synthesis of polycarbonates. Interpretation of the results of various acidity measurements (NH3 and pyridine desorption, methanol oxidation as a probe reaction) allowed us to identify the catalytic sites as Lewis acid sites.
Keywords: heterogeneous catalysis; Lewis acids; Oxidation; sol-gel processes; transesterification

Clay entrapped Cu(OH)(x) as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids - Dar, Bashir Ahmad; Bhatti, Prince; Singh, A. P.; Lazar, Anish; Sharma, Parduman R.; Sharma, Meena; Singh, Baldev (Applied Catalysis A-General, 2013)
A remarkably active, selective and stable montmorilonite-KSF entrapped Cu(OH)(x) catalyst, has been prepared for the ipso-hydroxylation of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst shows excellent reusability without leaching and any significant loss in catalytic activity. The catalyst was characterized using, XRD, SEM, TPR, IR, XPS and BET surface area measurement techniques. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: clay; Copper; heterogeneous catalysis; Phenols; Water chemistry

Disordered mesoporous V/TiO2 system for ambient oxidation of sulfides to sulfoxides - Negi, Sanjay Singh; Sivaranjani, Kumarsrinivasan; Singh, Anand Pal; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2013)
High sulfide conversion and predominant sulfoxide yield has been observed with 0.1% vanadium doped disordered mesoporous Ti1-xVxO2 material at ambient and sub ambient temperatures using environmentally green H2O2 oxidant. Ti1-xVxO2 materials were prepared by one-pot solution combustion method in less than 15 min and thoroughly characterized by X-ray diffraction, HRTEM, Raman spectra and other physicochemical techniques. Different sulfides, such as, phenylsulfide, methyl-p-tolylsulfide, ethylsulfide, thioanisole, were converted into the corresponding sulfoxide. Isolated V5+ incorporated in the TiO2 lattice is likely to be the active species for the sulfide oxidation reaction. Catalyst recycling studies indicates the robustness of the catalyst. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Ambient oxidation; Combustion synthesis; heterogeneous catalysis; Hydrogen peroxide; Mesoporous TiO2; Sulfoxidation; Sulfoxide

Functional and disordered meso-macroporous gamma-Al2-xMxO3 +/- y (M = Cu and/or Ce) - Gnanakumar, Edwin S.; John, Jino C.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2013)
Disordered meso-macro porous Cu-Ce-Al2O3 nanocomposite (gamma-Al2-xMxO3 +/- y, M = Cu and or Ce) with different compositions has been synthesized. In situ templated sol-gel method has been adopted with simple EDTA ethylenediamine tetra aceticacid and ethylenediamine molecules to prepare gamma-Al2-xMxO3 +/- y, (M = Cu and or Ce). Above meso-macro porous materials were characterized by structural, spectroscopy, microscopy and textural techniques. Detailed characterization indicates that Cu2+ ions are introduced into the ceria and alumina lattice positions. Nano composite nature of the gamma-Al2-xMxO3 +/- y has been confirmed by detailed microscopy investigations. Catalytic activity of the above nanocomposite materials have been screened for environmentally important CO oxidation reaction. 30% Ce-60% Al and 10% Cu containing material shows the best activity among other meso-nnacroporous material with (50%) 100% CO oxidation at (107 degrees C) 145 degrees C.
Keywords: Alumina; CO oxidation; heterogeneous catalysis; Meso-Macroporous Material; Nanocomposite; Sol-gel synthesis

Highly efficient povidone-phosphotungstic acid catalyst for the tandem acetalization of aldehydes to bis- and tris(indolyl)methanes - Kamble, Sumit B.; Swami, Rameshwar K.; Sakate, Sachin S.; Rode, Chandrashekhar V. (ChemPlusChem, 2013)
A novel, nonleachable hybrid of heteropoly acid and polyvinylpyrrolidone (or povidone) catalyzes the acetalization of aldehydes in methanol at room temperature followed by reaction with indole to give bis(indolyl)methanes (BIMs) and tris(indolyl)methanes (TIMs) in quantitative yields (90-97%). The catalyst was shown by pyridine FTIR spectroscopy to possess BrOnsted acidity, and the hybrid formation was confirmed by XRD and (PNMR)-P-31 studies. Friedel-Crafts alkylation of indole as well as the tandem synthesis of BIMs and TIMs were established with several types of carbonyl and indole substrates to give the corresponding products quantitatively. The catalyst was recycled efficiently for three successive runs without losing its original activity.
Keywords: acetals; Acidity; aldehydes; heterogeneous catalysis; heteropoly acids

Influence of method of preparation of solid, double-metal cyanide complexes on their catalytic activity for synthesis of hyperbranched polymers - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2013)
Catalytic activity of a series of Fe-Zn double-metal cyanide (DMC) complexes with varying structural and acidic properties has been investigated for the synthesis of hyperbranched polyesters (HPs) from glycerol and succinic acid/adipic acid. The DMC complexes were prepared using different complexing and co-complexing agents. Hydrophobicity of the surface, Lewis acidity and micro-mesoporous architecture are the critical features of DMC enabled control on gelation process in preparing HPs of high degree of branching. The micro-mesoporous architecture of DMC acts as a nano-reactor for reactant molecules to form primary condensation products which further polymerize yielding dendrimers. Hyperbranched polyesters of degree of branching as high as 90% could be achieved without gelation using DMC catalysts. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Dendrimers; Double-metal cyanide; heterogeneous catalysis; Hydrophobic solid acid catalyst; Hyperbranched polymers

Isolation, characterization, and identification of catalytically active species in the MoO3/SiO2 catalyst during solid acid catalyzed reactions - Kotbagi, Trupti V.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Chemcatchem, 2013)
We report the isolation, characterization, and identification of the catalytically active species formed during various acid-catalyzed reactions if silica-supported MoO3 was used as a catalyst. We have reported previously the synthesis and extensive characterization of the silica-supported MoO3 catalyst prepared by the sol-gel process with ammonium heptamolybdate and ethyl silicate-40 as molybdenum and silica precursors, respectively. The TEM images showed uniformly distributed MoO3 nanoparticles on the high-surface area mesoporous silica support and high acidity (0.9mmolg-1) by using temperature-programmed desorption of ammonia (NH3-TPD) analysis. This catalyst has already shown high activity for various acid-catalyzed reactions. To understand the nature of catalytically active species formed during the reaction, the liquid-phase esterification of acetic acid and ethanol was studied as a probe reaction with very high acid conversion (83%) in 8h. During esterification, the reaction mixture turned blue, which indicated a change in the nature of the catalyst under reaction conditions. These catalytically active species formed in the reaction mixture were isolated and extensively characterized by using FTIR, Raman, powder XRD, BET surface area, NH3-TPD, energy dispersive X-ray, and TEM analysis. The characterization results revealed the insitu formation of silicomolybdic acid on the silica surface in the presence of water, which acts as catalytically active species responsible for the acid-catalyzed reactions.
Keywords: esterification reactions; heterogeneous catalysis; Molybdenum; silicon; sol-gel processes

MgCl2 center dot 6CH(3)OH: a simple molecular adduct and its influence as a porous support for olefin polymerization - Gnanakumar, Edwin S.; Gowda, Ravikumar R.; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (ACS Catalysis, 2013)
A single phase molecular adduct, MgCl2 center dot 6CH(3)OH has been synthesized using MgCl2 and the simplest alcohol, methanol. Structural, spectroscopic, and morphological studies have been carried out for a better understanding of the single phase MgCl2 center dot 6CH(3)OH adduct. C-13 CPMAS solid state NMR studies show all six methanol molecules are magnetically equivalent and present in a single environment around the Mg2+ center. Raman spectral analysis of the characteristic peak at 708 cm(-1) substantiates octahedral coordination of six CH3OH molecules around Mg2+. Solid state C-13 NMR measurements, made after heat treatment at different temperatures, have been utilized to understand the variations in CH3OH stoichiometry and coordination around Mg2+ with temperature. A titanated active catalyst, TiCl4 on MgCl2 center dot 6CH(3)OH, has also been synthesized and subjected to detailed characterizations. The active catalyst shows high surface area (102 m(2)/g) and mesoporosity. The titanated catalyst has been screened for ethylene polymerization reactions using different cocatalysts (R3Al; R= -CH3, -CH2CH3, and -CH2CH(CH3)(2)). A total of 7.25 kg of polyethylene per gram of catalyst has been obtained with Me3Al cocatalyst, which is six times higher in activity compared with commercial Me3Al/TiCl4/MgCl2 center dot 6EtOH-supported orted catalystAlthough porosity influences the catalytic activity, other factors also seem to contribute to the total catalytic activity.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; olefin polymerization; Ziegler-Natta catalyst

Mixed Co-Mn oxide-catalysed selective aerobic oxidation of vanillyl alcohol to vanillin in base-free conditions - Jha, Ajay; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chempluschem, 2013)
Manganese-doped cobalt mixed oxide (MnCo-MO) catalyst was prepared by a solvothermal method. The as-prepared catalyst was characterised by X-ray photoelectron spectroscopy, H-2 temperature-programmed reduction, O-2 temperature-programmed oxidation and XRD. This catalyst gave 62% conversion with 83% selectivity to vanillin in 2hours for the liquid-phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified as Co3O4, Mn3O4 and CoMn2O4. Among these, the tetragonal phase of CoMn2O4 was found to be more active and selective for vanillyl alcohol oxidation than Co3O4 and Mn3O4. High-resolution TEM characterisation revealed the morphology of MnCo-MO nanorods with a particle size of 10nm. Successful recycling of the catalyst was also established in this oxidation reaction.
Keywords: aerobic oxidation; cobalt; heterogeneous catalysis; manganese; spinel phases

Modified zeolite immobilized palladium for ligand-free suzuki-miyaura cross-coupling reaction - Kumbhar, Arjun; Kamble, Santosh; Mane, Anand; Jha, Ratnesh Kumar; Salunkhe, Rajashri (Journal of Organometallic Chemistry, 2013)
A palladium-based catalyst supported on modified ZSM-5 was successfully prepared by a facile procedure. The prepared heterogeneous catalyst Pd@desilicated ZSM-5 showed an excellent catalytic activity at very low Pd loading (0.02 mol%) for the ligand-free Suzuki-Miyaura coupling reactions of various aryl bromides affording excellent yields of the products. The prepared catalyst presents good recyclability, over four catalytic cycles. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: heterogeneous catalysis; Suzuki-Miyaura reaction; zeolite

Chemically stable urea based COF for size selective heterogeneous catalysis - Basu, Arghya; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: chemical stability; Covalent organic framework; heterogeneous catalysis

Disordered mesoporous TiO2-xNx+Nano-Au: an electronically integrated nanocomposite for solar H-2 generation - Sivaranjani, Kumarsrinivasan; Rajaambal, Sivaraman; Das, Tanmay; Roy, Kanak; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
We report on H-2 generation by photocatalysis driven by simulated white light by electronically integrated Au nanoparticles with multifunctional, disordered mesoporous TiO2-xNx (Au-NT) nanocomposites. Solar H-2 generation (1.5 mmolh(-1)g(-1)) from aqueous methanol has been demonstrated with Au-NT nanocomposites. The water splitting activity of Au-NT is attributed to the 21.1 ps lifetime of charge carriers observed from fluorescence lifetime measurements, which indicates a high electron-injection efficiency from nano-Au to the conduction band of TiO2, and hence charge separation as well as utilization. This is directly supported by the observation of a high photoluminescence emission intensity with Au-NT that highlights the energy transfer from nano-Au to TiO2. The p-n heterojunction observed between the Au (001) and TiO2 (101) facets helps to-wards the higher charge separation and their utilization. A low mesochannel depth (< 10 nm) associated with disordered mesoporous TiO2-xNx helps the charge carriers to move towards the surface for redox reactions and hence charge utilization. Visible-light absorption, as a result of the surface plasmon resonance of nano-Au, is observed in a broad range between 500 and 750 nm, which helps in harvesting visible-light photons. Finally, electronically integrated nano-Au with TiO2-xNx in Au-NT is evident from Raman and X-ray photoelectron spectroscopy measurements. All of these factors help to achieve a high rate of H-2 production. It is likely that a higher rate of H-2 production than that reported here is feasible by strategically locating Au clusters in porous TiO2 to generate hot spots through electronic integration.
Keywords: heterogeneous catalysis; Hydrogen; mesoporous materials; photochemistry; water splitting

Nature of the active site in ziegler-natta olefin polymerization catalysis systems - a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (European Journal of Inorganic Chemistry, 2014)
Pull quantum chemical calculations with density functional theory (DET) show that a principal role of donors in Ziegler-Nana (ZN) oh-din polymerization catalysts is to coordinate to the metal center at the active sites on the MgCl2 surface. Thereby, the behavior of the catalyst is modulated to favor insertion over termination and, thus, polymerization occurs. This is shown to be true for a range of different donors. The calculations indicate that active sites that feature anionic chloride ligands at the titanium center (the conventional model for the active site) would lead to lower-molecular-weight riolymers. If an -OC2H5 group were present instead of a chloride ligand, the active site would much more effectively produce long chain polymers. Therefore, the current work provides important new insights into the nature of the ZN polymerization process.
Keywords: Alkene polymerization; Density functional calculations; heterogeneous catalysis; Insertion; Polymers

NOx reduction at near ambient temperatures and under lean-burn conditions on modified pd surfaces - Roy, Kanak; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
Palladium surfaces that are modified with O atoms in the subsurface broaden the NO reduction temperature regime up to 325 K with O-2-rich NO+H-2+O-2 compositions. Compared to virgin Pd surfaces, up to 150% higher deNO(x) catalytic activity was observed with modified Pd surfaces at the reaction maximum. Molecular beam instrument and ambient-pressure photoelectron spectroscopy were employed to follow the kinetic and surface changes. These results open up a possibility to realize the cold-start reduction of NOx (deNO(x)). DeNO(x) activity reported in the literature with supported Pd catalysts after a simple calcination in air compares well with our present observations. Surface modification is likely to demonstrate a high potential for other catalytic reactions at relatively low temperatures.
Keywords: heterogeneous catalysis; nitrogen; oxygen; Palladium; surface chemistry

Palladium nanoparticles supported on magnesium hydroxide fluorides: a selective catalyst for olefin hydrogenation - Acham, Vaibhav R.; Biradar, Ankush V.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (ChemCatChem, 2014)
A one-pot synthesis of palladium nanoparticles supported on magnesium hydroxide fluoride has been performed with the fluorolytic sol-gel method. The prepared catalysts were characterized by using various physicochemical techniques. The sol-gel method led to high surface area (>135 m(2)g(-1)), mesoporous catalysts (pore volume=0.19-0.23 cm(3)g(-1), pore diameter=3-5 nm) with uniformly dispersed palladium nanoparticles approximately 2 nm in diameter on the surface. The catalysts synthesized by using different concentrations of aqueous hydrofluoric acid exhibited changing surface and acidic properties. Very high dispersion of palladium on magnesium fluoride (47%) was obtained with 1 wt% palladium loading. The catalysts were used for hydrogenation of various olefins in the presence of other organic functionalities at room temperature and atmospheric hydrogen pressure. Various substituted olefins were hydrogenated with almost 100% conversion and selectivity. The catalysts were recycled efficiently over five cycles without appreciable loss in catalytic activity. There was no palladium leaching under the reaction conditions, which was confirmed by inductively coupled plasma atomic emission spectroscopy analysis. Activation of olefin on the catalyst surface could not be observed by in situ FTIR studies, indicating facile activation of hydrogen on the palladium supported on magnesium hydroxide fluoride.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; magnesium fluorides; Palladium

Role of nanointerfaces in Cu- and Cu plus Au-based near-ambient-temperature CO oxidation catalysts - Gnanakumar, Edwin S.; Naik, Jarpla Madhusudhan; Manikandan, Marimuthu; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
Disordered mesoporous Cu-doped ceria-zirconia (Cu0.1Ce0.85Zr0.05O2), and gold deposited (Au/Cu0.1Ce0.85Zr0.05O2) catalysts were synthesized and evaluated for CO oxidation. Onset of CO oxidation activity, and 50% (100%) CO2 formation occurs at room temperature (RT), and 77 (120)degrees C, respectively, with Cu0.1Ce0.85Zr0.05O2. A small amount of gold on Cu0.1Ce0.85Zr0.05O2 induces the sustainable oxidation catalysis around RT. Onset of copper reduction temperature decreases from 110 degrees C on Cu0.1Ce0.85Zr0.05O2 to 48 degrees C with Au/Cu0.1Ce0.85Zr0.05O2, highlighting the direct interaction between Cu and Au through a Cu-Au interface. Au particles with a (00 1) facet deposit on an oxygen-deficient site of (111) facet of CeO2-ZrO2. Any decrease in surface Cu-content with increasing Au-content further supports the Au-Cu-Ce/Zr interface interactions. Nanointerfaces of Au clusters on Cu next to oxygen-deficient sites of CeO2-ZrO2 facilitate all the elementary steps of the CO + O-2 reaction to occur in close proximity at ambient conditions.
Keywords: carbon monoxide; Gold; heterogeneous catalysis; Oxidation; redox

Solid, double-metal cyanide catalysts for synthesis of hyperbranched polyesters and aliphatic polycarbonates - Sebastian, Joby; Darbha, Srinivas (Journal of Chemical Sciences, 2014)
Fe-Zn and Co-Zn double-metal cyanide (DMC) complexes exhibit highly efficient and selective catalytic activity for synthesis of hyperbranched polyesters (glycerol succinic acid (G-SA) and glycerol adipic acid (G-AA)) and aliphatic polycarbonates (via., alternative co-polymerization of cyclohexene oxide and CO2), respectively. The influence of method of preparation of DMC, in particular the mode of addition of reagents, on its physicochemical and catalytic properties was investigated. Co-Zn DMC was found highly selective for polycarbonate (than polyethers) formation. Catalysts prepared using tert-butanol and PEG-4000 as complexing and co-complexing agents, respectively, were found superior to those prepared without these agents. Apart from its role as a coordinating ligand, tert-butanol activated the Lewis acidic Zn2+ sites for reactions in polyester and polycarbonate formation. Hydrophobicity, micro-mesoporosity, acid strength and the amount of coordinated complexing agent are some of the crucial factors influenced the catalytic activity of DMC complexes.
Keywords: aliphatic polycarbonate; CO2 utilization; Double-metal cyanide complex; heterogeneous catalysis; hyperbranched polyester

Structural investigations of porous MgCl2-2-butanol molecular adduct as support for olefin polymerization - Thushara, K. S.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2014)
A new heterogeneous Ziegler-Natta (Z-N) catalyst support material, MgCl2 center dot 4(CH3CH(OH)CH2CH3) (Mg2BuOH) has been synthesized. 2-Butanol, a linear, secondary alcohol was chosen for the generation of an active MgCl2 support which results in a Z-N catalyst with TiCl4. Significant feature of this work is the formation of rod shaped molecular adduct with highly porous character. Adduct material is characterized by XRD, TG-DTA, Raman spectroscopy, solid-state NMR and SEM. Activity of the Z-N catalyst supported on Mg2BuOH for ethylene polymerization is comparable with that of commercially available heterogeneous Z-N catalyst. However, there is scope to improve the activity by optimizing textural properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; NMR; Polyolefin; Ziegler-Natta catalyst

Towards a sustainable and near ambient DeNO(x) under lean burn conditions: a revisit to no reduction on virgin and modified pd(111) surfaces - Roy, Kanak; Jain, Ruchi; Gopinath, Chinnakonda S. (ACS Catalysis, 2014)
Catalytic conversion of NO in the presence of H-2 and O-2 has been studied on Pd(111) surfaces, by using a molecular beam instrument with mass spectrometry detection, as a function of temperature and reactants composition. N-2 and H2O are the major products observed, along with NH3 and N2O minor products under all conditions studied. Particular attention has been paid to the influence of O-2 addition toward NO dissociation. Although O-2-rich compositions were found to inhibit the deNO(x) activity of the Pd catalyst, some enhancement in NO reduction to N-2 was also observed up to a certain O-2 content. The reason for this behavior was determined to be the effective consumption of the H-2 in the mixture by the added O-2 and O atoms from NO dissociation. NO was proven to compete favorably against O-2 for the consumption of H-2, especially <= 550 K, to produce N-2 and H2O. Compared with other elementary reaction steps, a slow decay observed with the 2H + 0 -> H2O step under SS beam oscillation conditions demonstrates its contribution to the rate-limiting nature of the overall reaction. Pd(111) surfaces modified with O atoms in the subsurface (Md-Pd(111)) induces steady-state NO reduction at near-ambient temperatures (325 K) and opens up a possibility to achieve room temperature emission control. A 50% increase in the reaction rates was observed at the reaction maximum on Md-Pd(111), as compared with virgin surfaces. Oxygen adsorption is severely limited below 400 K, and effective NO + H-2 reaction occurs on Md-Pd(111) surfaces. Valence band photoemission with a UV light source (He I) under different oxygen pressures with APPES clearly identified the characteristics of the Md-Pd(111) surfaces and PdO. The electron-deficient or cationic nature of Md-Pd(111) surfaces enhances the NO dissociation and inhibits oxygen chemisorption <= 400 K under lean-burn conditions.
Keywords: deNO(x); heterogeneous catalysis; Hydrogen; lean burn; molecular beam; nitric oxide; Palladium; surface modification

Can we shift and/or broaden the catalysis regime towards ambient temperature? - Gopinath, Chinnakonda S.; Roy, Kanak; Nagarajan, Sankaranarayanan (ChemCatChem, 2015)
An attempt was made to shift the temperature regime of oxidation catalysis towards ambient temperatures by employing surface modification (SM) as a handle. Systematic SM of Pd(111) was performed by O-atom diffusion into the subsurfaces. Virgin and modified Pd(111) catalysts were evaluated for CO oxidation. Typical CO poisoning observed on virgin surfaces was partially lifted, and ambient CO oxidation was observed on the modified surfaces. CO oxidation was followed by the molecular beam method and near-ambient pressure (NAP) photoelectron spectroscopy under different pressure regimes. UV valence band spectral analysis of the SM and the CO+O-2 reaction on modified Pd(111) surfaces under NAP conditions demonstrated changes in the electronic structures of the surfaces with a change in surface potential by 0.35eV and directly probed CO2 formation under the reaction conditions. Supported metal catalysts may be subjected to SM and evaluated for a shift in the catalysis regime for many different reactions.
Keywords: heterogeneous catalysis; Oxidation; photoelectron spectroscopy; surface chemistry; surface modification

Catalytic upgrading of citric acid to environmental friendly tri-butyl citrate plasticizer over ultra stable phosphonated Y zeolite - Nandiwale, Kakasaheb Y.; Gogoi, Pranjal; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
The catalytic synthesis of non-toxic/eco-friendly tributyl citrate (TBC) plasticizer by esterification of renewable citric acid (CA) with butanol would be completely sustainable route. In this context, catalytic performance of parent ultra stable Y (USY) and phosphonated USY catalysts were investigated for TBC synthesis. Parent USY and phosphonated USY catalysts were characterized by powder X-ray diffraction (XRD), N-2 adsorption-desorption, NH3 temperature programmed desorption (TPD), pyridine-Fourier Transform Infrared Spectroscopy (FTIR), FTIR, SEM, ICP. The influence of various process parameters such as phosphorous (P) loading (0 to 4 wt/%), catalyst loading (5-25%), molar ratio of CA to n-butanol (1:4 to 1:12), reaction temperature (383-423 K) and reaction time (1-5 h) have been investigated over USY catalyst with aim to maximize CA conversion and TBC yield. Amongst the studied catalysts, the 2% (w/w) P/USY was found to be highly potential catalyst with complete CA conversion (100%) and 93% TBC yield. The present method of using 2% (w/w) P/USY catalyst for the synthesis of TBC would be environmentally benign in the context of bio-renewable synthetic route, high catalytic activity, non-toxic product, long term stability and reusability of catalyst (five catalytic cycles). (c) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved,
Keywords: Butanol; Citric acid; heterogeneous catalysis; Plasticizer; Tributyl citrate

SBA-15-oxynitrides as a solid-base catalyst: effect of nitridation temperature on catalytic activity - Singh, Baljeet; Mote, Kaustubh R.; Gopinath, Chinnakonda S.; Madhu, Perunthiruthy K.; Polshettiwar, Vivek (Angewandte Chemie-International Edition, 2015)
Solid bases, such as SBA-15-oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid-state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.
Keywords: heterogeneous catalysis; Nanostructures; NMR spectroscopy; photoelectron spectroscopy; solid-state structures

Sol-gel synthesised WO3 nanoparticles supported on mesoporous silica for liquid phase nitration of aromatics - Kulal, A. B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2016)
A series of WO3/SiO2 catalysts have been prepared by sol-gel method using ammonium metatungstate and ethyl silicate-40 (ES-40) as WO3 and SiO2 precursors respectively. The sol-gel method has led to the formation of WO3 nano-particles of 2-5 nm well dispersed on mesoporous silica along with some WO3' agglomerates. Formation of monoclinic WO3 was seen on the catalysts above 5 wt% WO3 loading by XRD analysis. Silica has shown very high surface area of 606 m(2)/g which decreased gradually upto 368 m(2)/g with 20 wt% WO3 loading. 20 wt% WO3/SiO2 catalyst has shown maximum acidity (0.56 mmol NH3/g) with presence of both Lewis and Bronsted acidity. UV-vis DRS analysis showed formation of polytungstate species along with WO3 on silica surface. The prepared catalysts were used for liquid phase nitration of aromatics using 70% nitric acid as nitrating agent without using any sulfuric acid. Very high conversion (99%) was obtained for p-cresol nitration with very high selectivity (99%) for 2-nitro p-cresol. The water formed during the reaction was removed azeotropically using ethylene dichloride as solvent. In case of o-xylene 74% conversion was obtained with 54% selectivity for 4-nitro o-xylene. The effect of different WO3 precursors on nitration efficiency was studied using sodium tungstate and tungstic acid as precursors. However,ammonium metatungstate showed the highest acidity. Sodium tungstate showed formation of dimer of sodium tungstate which did not show any acidity and hence no activity for nitration. The mechanism for nitration using WO3/SiO2 has been proposed based on polarisation of water on tungsten centre generating Bronsted acidity which can further generate nitronium ion giving subsequently nitration of the aromatic ring. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aromatic nitration; heterogeneous catalysis; Regioselective; Sol-gel synthesis; Water polarization

Versatile Cu-II metal-organic framework exhibiting high gas storage capacity with selectivity for CO2: conversion of CO2 to cyclic carbonate and other catalytic abilities - De, Dinesh; Pal, Tapan K.; Neogi, Subhadip; Senthilkumar, S.; Das, Debasree; Sen Gupta, Sayam; Bharadwaj, Parimal K. (Chemistry-A European Journal, 2016)
A linear tetracarboxylic acid ligand, H4L, with a pendent amine moiety solvothermally forms two isostructural metal-organic frameworks (MOFs) L-M (M=Zn-II, Cu-II). Framework L-Cu can also be obtained from L-Zn by post- synthetic metathesis without losing crystallinity. Compared with L-Zn, the L-Cu framework exhibits high thermal stability and allows removal of guest solvent and metal-bound water molecules to afford the highly porous, L-Cu. At 77K, L-Cu absorbs 2.57wt% of H-2 at 1bar, which increases significantly to 4.67wt% at 36bar. The framework absorbs substantially high amounts of methane (238.38cm(3)g(-1), 17.03wt%) at 303K and 60bar. The CH4 absorption at 303K gives a total volumetric capacity of 166cm(3)(STP)cm(-3) at 35bar (223.25cm(3)g(-1), 15.95wt%). Interestingly, the NH2 groups in the linker, which decorate the channel surface, allow a remarkable 39.0wt% of CO2 to be absorbed at 1bar and 273K, which comes within the dominion of the most famous MOFs for CO2 absorption. Also, L-Cu shows pronounced selectivity for CO2 absorption over CH4, N-2, and H-2 at 273K. The absorbed CO2 can be converted to value-added cyclic carbonates under relatively mild reaction conditions (20bar, 120 degrees C). Finally, L-Cu is found to be an excellent heterogeneous catalyst in regioselective 1,3-dipolar cycloaddition reactions (click reactions) and provides an efficient, economic route for the one-pot synthesis of structurally divergent propargylamines through three-component coupling of alkynes, amines, and aldehydes.
Keywords: click reactions; CO2 absorption; cyclic carbonate; heterogeneous catalysis; metal-organic frameworks

Environmentally benign bioderived carbon microspheres-supported molybdena nanoparticles as catalyst for the epoxidation reaction - Doke, Dhananjay S.; Umbarkar, Shubhangi B.; Gawande, Manoj B.; Zbori, Radek; Biradar, Ankush V. (ACS Sustainable Chemistry & Engineering, 2017)
A one pot synthesis of molybdenum oxide nanoparticles (NPs supported on bioderived carbon microspheres is reported. The catalyst was synthesized by the low temperature hydrothermal (LTH) method using D-glucose and bagasse as the carbon source. The carbonization of bagasse resulted in the formation of nonuniform carbon microspheres while glucose resulted in uniform carbon spheres. SEM and STEM elemental mapping show the uniform distribution of molybdenum oxide NPs over the carbon microspheres. XPS spectroscopy confirmed that molybdenum was in the Mo6+ oxidation state. The 1% MoO3 supported on carbon microspheres derived from D-glucose showed excellent catalytic activity up to 100% olefin conversion with 100% epoxide selectivity using organic tent-butyl hydroperoxide as an oxidant. The catalyst was successfully used for up to five cycles without losing substantial activity and selectivity.
Keywords: Carbon microspheres; epoxidation; heterogeneous catalysis; Hydrothermal synthesis; TBHP

Exploration of amination reactions on highly extendable active sites of Pd(II)-3-allylsalicylaldiminophenol (ASIP) complex over thiofunctionalized SBA-15 - Lazar, Anish; Vinod, C. P.; Singh, A. P. (Microporous and Mesoporous Materials, 2017)
An effective and impressive heterogeneous catalyst, Pd(II)-3-allylsalicylaldiminophenol-SBA-15, dubbed as Pd(II)ASIP@SBA-15, for amination reactions of aryl halides to synthesize secondary amines (2), has been synthesized and characterized. Pd(II)ASIP@SBA-15 has been synthesized by the covalent anchoring of 3-allylsalicylaldehyde over thiofunctionalized SBA-15, then further reaction with 2-aminophenol, followed by metallation process by using Pd(11)(OAc)(2). A specifically designed cheap and easily available organic ligand, 3-allylsalicylaldiminophenol (ASIP), was synthesized from 3-allylsalicylaldehyde and 2-aminophenol. Using this, the synthesis of Pd(II)ASIP@SBA-15 was carried out whereby the ligand providing an active co-ordination or chelating sites for palladium metal. This strategy helped in exposing the Pd(11)ASIP active sites from surface to channels of SBA-15 support during the reactions. The synthesized catalyst were characterized by CHN analysis, PXRD, Nitrogen sorption analyses, TG & DTA, FTIR, C-13 and Si-29 CPMASS NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. Pd(II)ASIP@SBA-15 catalyst was screened in heterogeneous amination reactions of aryl halides to produce N-aryl derivatives or secondary amines with high catalytic activity as revealed by turn over frequency (TOF) calculations. To explore the heterogeneous nature of catalysts, amination reactions were carried with neat Pd(II)ASIP complex and Pd(11)(OAc)(2) catalysts. The catalyst was recycled several times without much loss of activity and Sheldon hot filtration test has been performed. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Amination Reactions; heterogeneous catalysis; Reusable; Supported catalysis

Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts

Subtle interaction between Ag and O 2 : a near ambient pressure UV photoelectron spectroscopy (NAP-UPS) investigations - Ghosalya, Manoj Kumar (Journal of Chemical Sciences, 2018)
The Ag-O2 interaction, which is at the center-stage of Ag-catalyzed partial oxidation reactions, is studied with NAP-UPS up to 0.2 mbar O2 pressure between 295 and 550 K. Three temperature regimes were identified for distinct Ag-O2 interaction, which are (a) 295–390 K, where mainly dissociative chemisorption of O2 happens, (b) 390–450 K, where diffusion of O-atoms into the sub-surfaces of Ag is prominent, and (c) >450 K, where metastable oxide forms on polycrystalline Ag surfaces. The work function (WF) of Ag changed from 4.95 (≤390 K) to 5.30 eV (390–450 K), and then to 5.7 eV (≥450 K) at 0.1 mbar O2 pressure. Oxygen population in the sub-surfaces imparts crucial modifications to Ag at 390–450 K; it makes the surface to be electron-deficient that relates to the change in the WF of Ag and facilitates the formation of space charge layer on Ag surface. Oxygen adsorbed on such modified Ag-surfaces is electrophilic in nature, and this appears at a higher binding energy in core level XPS than the chemisorbed oxygen on metallic Ag. This is supported by angle-dependent NAP-XPS studies. The subsurface population of oxygen in Ag no longer persists at >410 K when the O2 supply is removed. A high ratio of antibonding/bonding O 2p bands suggests the unique silver-oxygen interaction under the measurement conditions.
Keywords: Electronic Structure; epoxidation; heterogeneous catalysis; Surface Science

Acidic handle assemble heterogeneous carbocatalyst for facile aliphatic nucleophilic fluorination - Said, Madhukar S.; Pandole, Satish; Suryavanshi, Amol; Kumar, Pradeep; Gajbhiye, Jayan M. (ChemistrySelect, 2019)
Acidic handle (-SO3H) assemble carbonaceous catalyst synthesized from glucose acts as a modulator for the nucleophilic fluorination reaction. The heterogeneous catalyst works with various alkyl sulfonate, halide and metal fluoride (MF), to offer a high yield of fluorinated products up to 93%. This carbonaceous catalyst is recyclable for more than five times, with no major loss of activity.
Keywords: fluorination; heterogeneous catalysis

Click chemistry based multicomponent approach in the synthesis of spirochromenocarbazole tethered 1,2,3-triazoles as potential anticancer agents - Chavan, V, Pramod; Desai, V, Uday; Wadgaonkar, Prakash P.; Tapase, Savita R.; Kodam, Kisan M.; Choudhari, Amit; Sarkar, Dhiman (Bioorganic Chemistry, 2019)
A series of spirochromenocarbazole tethered 1,2,3-triazoles were synthesized via click chemistry based one-pot, five component reaction between N-propargyl isatins, malononitrile, 4-hydroxycarbazole, aralkyl halides and sodium azide using cellulose supported CuI nanoparticles (Cell-CuI NPs) as the heterogeneous catalyst. Antiproliferative activity of all the synthesized compounds was investigated against panel of cancer cell lines such as MCF-7, MDA-MB-231, HeLa, PANG-1, A-549, and THP-1. Many of the synthesized compounds exhibited good anti-proliferative activity against breast (MCF-7 and MDA-MB-231) and cervical (HeLa) cancer cells with IC50 values less than 10 mu M. In case of MCF-7 cells, among the nine compounds that showed good anti-proliferative activity, compounds 6f and 6j were found to be highly potent (IC50 , = 2.13 mu M and 4.80 mu M, respectively). In case of MDA-MB-231, three compounds (6k, 6j and 6s) showed antiproliferative activity amongst which 6k was the most potent one (IC50 = 3.78 mu M). On the other hand, in cervical cancer HeLa cells, compounds 6b, 6g, 6s and 6u showed excellent antiproliferative activity (IC50 = 4.05, 3.54, 3.83, 3.35 mu M, respectively). All the compounds were found to be nontoxic to the human umbilical vein endothelial cells (HUVECs). AO and EtBr staining and fluorescence microscopy studies of the active compounds (IC50 < 5 mu M) suggested that these compounds induce cell death by apoptosis.
Keywords: 1; 2; 3-Triazolylspirochromenocarbazole; Anticancer; Apoptotic assay; Click chemistry; Cytotoxicity; heterogeneous catalysis; Multicomponent synthesis

Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes

Epoxidation of karanja (Millettia pinnata) oil methyl esters in the presence of hydrogen peroxide over a simple niobium-containing catalyst - Scotti, Nicola; Ravasio, Nicoletta; Evangelisti, Claudio; Psaro, Rinaldo; Penso, Michele; Niphadkar, Prashant S.; Bokade, Vijay V.; Guidotti, Matteo (Catalysts, 2019)
The synthesis, characterization and catalytic performance of a conceptually simple, novel NbOx-SiO2 catalyst are here described. The niobium(V)-silica catalyst was prepared starting from cheap and viable reactants, by alkaline deposition of NH4Nb(C2O4)(2)H2O in the presence of fructose as a stabilizer and subsequent calcination. The NbOx-SiO2 solid (0.95 Nb wt.%) was tested in the liquid-phase epoxidation with aqueous hydrogen peroxide of methyl oleate, as a model substrate. It was then tested in the epoxidation of a mixture of methyl esters (FAMEs) obtained by transesterification with methanol and purification of karanja oil, extracted from the autochthonous Indian variety of Millettia pinnata tree. The catalyst showed a promising performance in terms of methyl oleate conversion (up to 75%) and selectivity to epoxide (up to 82%). It was then tested on the FAME mixture from karanja oil, where interesting conversion values were attained (up to 70%), although with lower selectivities and yields to the mixture of desired epoxidized FAMEs. The solid withstood four catalytic cycles overall, during which a non-negligible surface reorganization of the Nb(V) sites was observed. However, this restructuring did not negatively affect the performance of the catalysts in terms of conversion or selectivity.
Keywords: epoxidation; fatty acid methyl esters; heterogeneous catalysis; Hydrogen peroxide; karanja oil; mesoporous silica catalyst; Millettia pinnata; niobium catalysts

Glycine-induced electrodeposition of nanostructured cobalt hydroxide: a bifunctional catalyst for overall water splitting - Shilpa, Nagaraju; Nadeema, Ayasha; Kurungot, Sreekumar (ChemSusChem, 2019)
Herein, an interconnected alpha-Co(OH)(2) structure with a network-like architecture was used as a bifunctional electrocatalyst for the overall water splitting reaction in alkaline medium. The complexing ability of glycine with a transition metal was exploited to form [Co(gly)(3)](-) dispersion at pH 10, which was used for the electrodeposition. High-resolution TEM, UV/Vis-diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy were used to confirm that the as-synthesized materials had an alpha-Co(OH)(2) phase. The electrocatalytic oxygen and hydrogen evolution activity of the glycine-coordinated alpha-Co(OH)(2) was found to be approximately 320 and 145 mV, respectively, at 10 mA cm(-2). The material required approximately 1.60 V (vs. reversible hydrogen electrode; RHE) to achieve the benchmark of 10 mA cm(-2) for overall water splitting with a mass activity of approximately 63.7 A g(-1) at 1.60 V (vs. RHE). The chronoamperometric response was measured to evidence the stability of the material for overall water splitting for up to 24 h. Characterization of the catalyst after the oxygen and hydrogen evolution reactions was performed by XPS and showed the presence of a Co-II/Co-III oxidation state.
Keywords: cobalt; Electrochemistry; heterogeneous catalysis; Hydrogen; water splitting

Hydrophobic WO3/SiO2 catalyst for the nitration of aromatics in liquid phase - Kulal, A. B.; Kasabe, M. M.; Jadhav, P. V.; Dongare, M. K.; Umbarkar, S. B. (Applied Catalysis A-General, 2019)
WO3/SiO2 solid acid catalyst synthesized using sol gel method has shown promising activity (up to 65% conversion) for aromatic nitration in liquid phase using commercial nitric acid (70%) as nitrating agent without using any sulfuric acid. The water formed during the reaction as well as water from dilute nitric acid (70%) was removed azeotropically, however due to the hydrophilic nature of the catalyst, some water gets strongly adsorbed on catalyst surface forming a barrier layer between catalyst and organics. This prevents effective adsorption of substrate on catalyst surface for its subsequent reaction. To improve the activity further, the hydrophilic/hydrophobic nature of the catalyst was altered by post modification by grafting with commercial short chain organosilane (Dynasylan 9896). The modified 20% WO3/SiO2 catalyst when used for o-xylene nitration in liquid phase, showed significant increase in the conversion from 65% to 80% under identical reaction conditions. Catalyst characterization revealed decrease in the surface area of 20% WO3/SiO2 from 356 m(2)/g to 302 m(2)/g after grafting with Dynasylan 9896. The fine dispersion of WO3 particles (2-5 run) on silica support was not affected due to modification. NMR and FTIR study revealed the decrease in surface hydroxyl groups imparting hydrophobicity to the catalyst. Interestingly the total acidic sites of the catalyst remained almost unaltered (0.54 mmol NH3/g) even after modification. Even though, the acidity and other characteristics of the catalyst did not change appreciably, there was a considerable increase in the o-xylene conversion which can be ascribed to the hydrophobic nature of the catalyst.
Keywords: Aromatic nitration; grafting; heterogeneous catalysis; Hydrophobic; Sol-gel synthesis

Selective hydrogenolysis of 5-(hydroxymethyl)furfural over Pd/C catalyst to 2,5-dimethylfuran - Solanki, B. S.; Rode, C. V. (Journal of Saudi Chemical Society, 2019)
everal metal supported catalysts were prepared and evaluated for 5-(hydroxymethyl)furfural (5-HMF) hydrogenolysis to 2,5-dimethylfuran (2,5-DMF) which is a renewable potential fuel additive. Among the prepared catalysts, 3%Pd/C showed excellent performance in terms of complete conversion of 5-HMF along with the highest selectivity of 99% to 2,5-DMF. Detailed physico-chemical characterisation was done in order to understand structure-activity correlation. Uniformly dispersed Pd nanoparticles on activated carbon provided the adsorption surface to enhance the hydrogenation of 5-HMF. Reaction was well optimised and established by extensive study of different reaction parameters like temperature, pressure, reaction time, stirring effect, substrate loading and metal loading.
Keywords: Biomass; Fuel additive; heterogeneous catalysis; Hydrogenolysis; Palladium

Boron nitride and oxide supported on dendritic fibrous nanosilica for catalytic oxidative dehydrogenation of propane - Belgamwar, Rajesh; Rankin, Andrew G. M.; Maity, Ayan; Mishra, Amit Kumar; Gomez, Jennifer S.; Trebosc, Julien; Vinod, Chathakudath P.; Lafon, Olivier; Polshettiwar, Vivek (ACS Sustainable Chemistry & Engineering, 2020)
In this work, we were able to significantly increase the activity of boron nitride (BN) catalysts used for the oxidative dehydrogenation (ODH) of propane by designing and synthesizing BN supported on dendritic fibrous nanosilica (DFNS). DFNS/BN showed a markedly increased catalytic efficiency, accompanied by exceptional stability and selectivity. Textural characterization, together with solid-state nuclear magnetic resonance (NMR) and X-ray photoelectron spectroscopic analyses, indicates the presence of a combination of unique fibrous morphology of DFNS and various boron sites connected to silica to be the reason for this increase in the catalytic performance. Notably, DFNS/B2O3 also showed catalytic activity, although with more moderate selectivity compared to that of DFNS/BN. Solid-state NMR spectra indicate that the higher selectivity of DFNS/BN might stem from a larger amount of hydrogen-bonded hydroxyl groups attached to B atoms. This study indicates that both boron nitride and oxide are active catalysts and by using high surface area support (DFNS), conversion from propane to propene as well as productivity of olefins was significantly increased.
Keywords: Electron microscopy; heterogeneous catalysis; Nanostructures; NMR spectroscopy; propane dehydrogenation; X-ray diffraction; X-ray photoelectron spectroscopy

Electronic structure evolution of Pd@Co nanocatalysts under oxidation and reduction conditions and preferential CO oxidation - Jain, Ruchi; Gopinath, Chinnakonda S. (ChemCatChem, 2020)
Herein, we present the surface electronic structure and morphological evolution under reduction and oxidation conditions for Pd@Co (PC) core-shell nanoparticles with different Pd : Co ratio (PC=2 : 1, 1 : 1 and 1 : 2). Extensive measurements have been made with NAPXPS (near ambient pressure x-ray photoelectron spectroscopy) under oxidising and reducing conditions, and ex-situ HRTEM. It has been demonstrated that PC catalysts are thermally stable towards morphological changes, at least up to 575 K. Nonetheless, it shows a significant surface electronic structure changes under reaction environments, which are highly relevant to heterogeneous catalysis. As expected, high (low) population of metallic (oxidised) Co was observed, while retaining core shell structure under reduction (H(2)and vacuum annealing) environment. Interestingly, the Pd-Co metallic interface helps to overcome the pyrophoric nature of cobalt and stabilised a significant amount of metallic Co at Pd-Co interface even in the presence of 0.1 mbar O(2)up to 575 K. The presence of Pd-Co and Pd-Co@Co(3)O(4)interfaces in reaction environment makes the catalyst dual functional. The proof of concept has been explored in terms of oxidation of CO in the presence of H(2)or O-2.
Keywords: Core-Shell morphology; Electronic Structure; heterogeneous catalysis; interface; XPS

Active and recyclable gold metal nanoparticles catalyst supported on nitrogen-doped mesoporous carbon for chemoselective hydrogenation of cinnamaldehyde to cinnamyl alcohol - Nagpure, Atul S.; Gogoi, Pranjal; Chilukuri, Satyanarayana V. (Chemistry-An Asian Journal, 2021)
Several supported gold metal catalysts with different Au nanoparticles sizes were prepared and evaluated for the chemoselective hydrogenation of cinnamaldehyde (CA) to cinnamyl alcohol (CAL). To investigate the structure-activity relationship, stability of catalyst, heterogeneity and recyclability, the structural characteristics of materials and Au catalysts (fresh and spent catalysts) were studied by employing variety of physico-chemical techniques. The interrelationship among Au nanoparticles size (nm) with turnover frequency (h(-1)) of Au catalysts has also been explored. Among the various Au catalysts tested, nitrogen-doped mesoporous carbon (NMC) supported Au catalyst having homogeneously dispersed (78.8%) Au nanoparticles (1.6 nm) synthesized by sol-immobilization method (Au-NMC-SI) demonstrated improved catalytic activity affording 78% CAL selectivity and 94.2% CA conversion without using any promoter. Moreover, Au-NMC-SI catalyst exhibited good recyclability and stability. The catalyst synthesis approach described in this investigation opens up a novel strategy for the design of highly efficient metal nano-catalysts supported on NMC materials.
Keywords: Au Nanoparticles; heterogeneous catalysis; Hydrogenation; Nitrogen-doped mesoporous carbon; Support-Metal interaction

Aqueous methanol to formaldehyde and hydrogen on Pd/TiO2 by photocatalysis in direct sunlight: structure dependent activity of nano-Pd and atomic Pt-coated counterparts - Nalajala, Naresh; Salgaonkar, Kranti N.; Chauhan, Inderjeet; Mekala, Siva Prasad; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2021)
In the present investigation, facet-controlled Pd nanoparticles with nanocube (Pd-NC) and truncated octahedron (Pd-TO) morphologies, and their counterparts with half-a-monolayer of atomic Pt coated (0.5 theta(Pt)-Pd-NC and 0.5 theta(Pt)-Pd-TO) surfaces were prepared. All of them were characterized and evaluated as cocatalyst after supporting them on commercial titania (P25) (Pd-NC/P25, Pd-TO/P25, 0.5 theta(Pt)-Pd-NC/P25, and 0.5 theta(Pt)-Pd-TO/P25) under direct sunlight and/or one sun conditions for the oxidation of methanol to formaldehyde along with solar hydrogen production. Pd-NC/P25 shows higher activity for hydrogen generation compared to Pd-TO/P25; however, activity reversal occurs with the above cocatalysts, but, after Pt-coating with further enhanced activity. The highest conversion of methanol (0.2 mu mol/h.mg) to 100% selective formaldehyde was observed with 0.5 theta(Pt)-Pd-TO/P25, while other catalysts show significantly lower methanol conversion in the following order: 0.5 theta(Pt)-Pd-TO/P25 > 0.5 theta(Pt)-Pd-NC/P25 > Pd-NC/P25 > Pd-TO/P25. Pt-coated on (111) facets of Pd-TO simulates the activity associated as that of Pt(111) facets and demonstrating the highest and facet dependent activity. The present study is truly in resonance with exploiting the surface properties for heterogeneous catalysis, and highlights that less than a monolayer of Pt is sufficient to simulate the activity as that of bulk Pt. It is worth exploring this concept to other metals and substrates too.
Keywords: heterogeneous catalysis; Nanomaterials; Oxidation; Photocatalysis; surface modification

Catalytic applications of hydrotalcite and related materials in multi -component reactions: concepts, challenges and future scope - Burange, Anand S.; Gopinath, Chinnakonda S. (Sustainable Chemistry and Pharmacy, 2021)
Hydrotalcites (HTs) are the potential substitute to conventional base catalysts. HTs are useful in efficient syntheses of various heterocycles, such as chromenes, pyrans, pyrazoles, triazoles, using multi-component reactions. This review focuses on the chemistry of HTs and particularly hydrotalcites and related materials in the synthesis of heterocycles. The effects of preparation method and, physico-chemical parameters, such as calcination, molar ratio of metals, role of intercalated ions, surface area, on the catalytic activities are discussed. Along with technical aspects, this review also unlocks various untouched areas in developing sustainable catalyst for syntheses of heterocycles, drugs, etc. for the future.
Keywords: green chemistry; green synthesis; heterocycles; heterogeneous catalysis; hydrotalcite; Metal Oxide

Electronically integrated mesoporous Ag-TiO2 nanocomposite thin films for efficient solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Nalajala, Naresh; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Technology, 2021)
The synthesis of mesoporous TiO2 by a solution-based assembly process and Ag/TiO2 nanocomposites is provided. The efficacy of Ag/TiO2 nanocomposite as photocatalyst in thin-film form is demonstrated for solar hydrogen generation in sunlight. Integration of Ag with TiO2 dramatically enhanced the H-2 production: with 1 wt% Ag on TiO2 (TiAg-1), the H-2 yield was observed to be 4.59 mmol h(-1) g(-1), which is 2.3 (30) times larger than 0.5 wt% Ag on TiO2. TiAg-1 shows 4.3 times higher activity in film form compared with its powder counterpart. High photocatalytic efficiency is attributed to the surface plasmon resonance effect of Ag, electronic integration of Ag with TiO2, and subsequent valence band broadening, large distribution of Ag nanoparticles and abundant Ag-TiO2 Schottky junctions, and the later minimizes electron-hole recombination. Interparticle mesoporous network increases necking and the high surface area offers easy accessibility of the reactants to a large number of active sites.
Keywords: heterogeneous catalysis; heterojunctions; plasmon effect; Silver; solar energy conversion; Solar hydrogen

Green synthesis of xanthene and acridine-based heterocycles of pharmaceutical importance: a review - Burange, Anand S.; Gadam, Komal G.; Tugaonkar, Prajyot S.; Thakur, Seema D.; Soni, Ravish K.; Khan, Rubej R.; Tai, Mubashira S.; Gopinath, Chinnakonda S. (Environmental Chemistry Letters, 2021)
Xanthene and acridine-based heterocyclic compounds find applications in cancer chemotherapy, biological staining and laser dyes and are known for their antibacterial and anti-tumor properties. Here we review green catalytic routes for the synthesis of 1,8-dioxo-octahydroxanthenes, 1,8-dioxo-decahydroacridines and related heterocyclic molecules with catalysts such as metal oxides, mixed metal oxides, resins, supported organocatalysts, heteropolyacids, carbon-based materials, zeolites, sulfides and ionic liquids. We compare protocols for their catalytic activities, and proposed mechanisms are discussed.
Keywords: green chemistry; heterocycles; heterogeneous catalysis; Metal oxides; nanocatalysis

Single-pot alcoholysis of furfuryl alcohol to alkyl levulinates using heterogenized p-TSA catalyst** - Patil, Chetana R.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (ChemistrySelect, 2021)
Synthesis of levulinate esters which are known to be excellent sustainable fuel additives, was achieved by alcoholysis of furfuryl alcohol over strong solid acid catalyst, prepared by copolymerization of p-toluenesulfonic acid with paraformaldehyde. Our catalyst possessed Bronsted acidity (3 mmol/g) with an excellent stability up to 220 degrees C. XPS, FT-IR and Pyridine-IR along with microanalysis studies confirmed the presence of terminal -SO3H functional groups responsible for Bronsted acidity in the catalyst. The catalyst was found to efficiently catalyze the alcoholysis of furfuryl alcohol to give alkyl levulinates under mild reaction conditions. The complete conversion of furfuryl alcohol with 96 % and 97 % selectivities to ethyl and butyl levulinates could be achieved using ethanol and butanol, respectively. Detailed study on effect of various reaction parameters like catalyst loading, reaction time and reaction temperature on conversion and product distribution was also carried out for the ethanolysis of furfuryl alcohol to ethyl levulinate. The catalyst could be easily recovered and recycled for five times successfully, with no loss in its original activity.
Keywords: Biomass; ethyl levulinate; Fuel additive; Furfuryl alcohol; heterogeneous catalysis

Sulfonic acid-functionalized heterogeneous catalytic materials for efficient biodiesel production: a review - Tan, Xiang; Sudarsanam, Putla; Tan, Jinyu; Wang, Anping; Zhang, Heng; Li, Hu; Yang, Song (Journal of Environmental Chemical Engineering, 2021)
The development of social productive forces leads to the increasing consumption of fossil fuels. However, the burning of traditional fossil fuels releases huge amounts of carbon emissions into the atmosphere, resulting in drastically increased global surface temperatures, and hence, global warming and abnormal climate change. Biodiesel, which can be produced by (trans)esterification of bio-oils using solid acid catalysts, is recognized as renewable and clean energy, alternative to fossil-derived diesel, and it can meet society's requirements. This review describes the catalytic conversion of bio-derived oils into biodiesel using various sulfonic acid-functionalized heterogeneous catalytic materials that show higher catalytic efficiency and superior recyclability. Besides, various methods of biodiesel preparation and the appropriate design and preparation of robust and efficient catalytic materials for biodiesel production were provided. Finally, the mechanisms of different catalytic esterification and transesterification reactions for biodiesel synthesis, the relevant reaction kinetic models, and techno-economic analysis of biodiesel production were critically discussed in this review.
Keywords: (Trans)esterification; Biodiesel; heterogeneous catalysis; kinetic study; solid acid

Sustainable CO2 reduction on in (2)O(3 )with exclusive CO selectivity: catalysis and in situ valence band photoelectron spectral investigations - Mhamane, Nitin B.; Chetry, Sibo; Ranjan, Ravi; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2022)
This study demonstrates a sustainable catalytic CO2 conversion to near 100% CO selectivity at ambient pressure on In2O3. Critically, high CO yield could be observed at the cost of undesired methanation, using a lower than stoichiometric amount of hydrogen in the feed; 1:1 and 1:0.67 CO2:H-2 ratios exhibit 98-99.6% CO selectivity with 25-38% CO2 conversion between 773 and 873 K. CO2 and H-2 conversion under steady-state conditions at 773-873 K suggests a 1:1 ratio of adsorbed reactants (with 1:0.67 CO2:H-2 feed) on the catalyst surface, underscoring the presence of an ideal reactant composition for the reverse water-gas shift reaction, while H-2-rich feed compositions show the H-2-dominated surface. Surface electronic structure changes, under near-operating conditions, were explored with near ambient pressure photoelectron spectroscopy (NAPPES), and the interesting findings are as follows: (a) A shift in the valence band to lower binding energy, up to 0.6 eV, was observed because of electron filling at high temperatures. (b) An observation of heterogeneous nature of the catalyst surface under NAPPES measurement conditions is attributed to the generation of active oxygen vacancy (O-v) sites, which in turn changes the work function of In2O3. (c) The above changes are found to be reversible, when the reaction was stopped. Vibrational features of the reactant molecules were observed to be broadened in the active temperature window of the catalyst supporting the heterogeneous character of the catalyst surface because of dynamic O-v generation. By optimizing gas hourly space velocity, CO2:H-2 ratio, and reaction temperature, exclusive CO selectivity is possible with a H-2:CO2 ratio of similar to 0.67, which will avoid the product separation stage altogether, while minimizing the expensive H-2 in the reactant feed.
Keywords: heterogeneous catalysis; Oxygen vacancy; photoelectron spectroscopy; RWGS; Work function

Can Li atoms anchored on boron- and nitrogen-doped graphene catalyze dinitrogen molecules to ammonia? a DFT study - Verma, Tushar Singh; Samal, Pragnya Paramita; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (ChemPhysChem, 2023)
The most successful electrochemical conversion of ammonia from dinitrogen molecule reported to date is through a Li mediated mechanism. In the framework of the above fact and that Li anchored graphene is an experimentally feasible system, the present work is a computational experiment to identify the potential of Li anchored graphene as a catalyst for N-2 to NH3 conversion as a function of (a) minimum number of Li atoms needed for anchoring on graphene sheets and (b) the role of chemical modification of graphene surfaces. The studies bring forth an understanding that Li anchored graphene sheets are potential catalysts for ammonia conversion with preferential adsorption of N-2 through end-on configuration on Li atoms anchored on doped and pristine graphene surfaces. This mode of adsorption being characteristic of Nitrogen Reduction Reaction (NRR) through enzymatic pathway, examination of the same followed by analysis of electronic properties demonstrates that tri-Li atoms (Tri Atom Catalysts, TACs) are more efficient as catalysts for NRR as compared to two Li atoms (Di Atom Catalysts, DACs). Either way, the rate determining step was found to be *NH2 ->*NH3 step (mixed pathway) with Delta G(max)=1.02 eV and *NH2-*NH3 ->*NH2 step (enzymatic pathway) with Delta G(max)=1.11 eV for 1B doped TAC and DAC on graphene sheet, respectively. Consequently, this work identifies the viability of Li anchored graphene based 2-D sheets as hetero-atom catalyst for NRR.
Keywords: computational chemistry; Graphene Sheet; heterogeneous catalysis; Li Nanoparticles; Nitrogen Reduction Reaction

Co3O4 for sustainable CO2 reduction and possible fine-tuning towards selective CO production - Ranjan, Ravi; Tekawadia, Jyoti; Jain, Ruchi; Mhamane, Nitin B.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2023)
Two main challenges involved in heterogeneous catalytic CO2 reduction are: (a) decreasing the consumption of H2 to the minimum required level with possibly the maximum CO2 conversion, and (b) concurrently enhancing the selectivity of the desired CO, at the cost of methane. Towards meeting these two challenges, Co3O4 spinel has been identified as a potential catalyst and it exhibits predominant CO selectivity > 673 K at atmospheric pressure. CO2 conversion begins > 523 K, with 100% CO selectivity observed > 673 K with CO2:H2 = 3:2. Current work shows a sustainable catalytic CO2 conversion to 100% CO selectivity with Co3O4-Nanocube (NC). Critically, CO selectivity and yield is observed to increase at the cost of methane with smaller amount of H2. 1:1 and 3:2 CO2:H2 ratio exhibits 88-100% CO selectivity with 24-32.5% CO2 conversion between 623 and 823 K. Irrespective of the input CO2:H2, ratio of CO2:H2 uptake changes from around 1:3 at 523 K to 1:1-1.5 at 823 K with concurrent production of significant methane to predominant CO, respectively. Surface electronic state changes was explored by near ambient pressure photoelectron spectroscopy, and the results suggests that Co3O4 is the active phase that promotes CO2 reduction selectively to CO. Broadening observed with the vibrational feature of the CO2 molecules at high temperature underscores the heterogeneous character of the catalyst surface, under operating conditions, due to changing electron density. By optimizing the gas hourly space velocity (GHSV), H2-lean CO2:H2 ratio, and the reaction temperature/pressure, 100% CO selectivity could be broadened to a range of operating conditions.
Keywords: Carbon neutral economy; heterogeneous catalysis; RWGS; SDG; Surface Science

Direct conversion of N-acetyl-d-glucosamine to N-containing heterocyclic compounds 3-acetamidofuran and 3-acetamido-5-acetyl Furan - Shaikh, Samrin S.; Patil, Chetana R.; Lucas, Nishita; Bokade, Vijay V.; Rode, Chandrashekhar V. (Waste and Biomass Valorization, 2023)
Purpose Effectual waste utilization from plant as well as marine biomass has gained tremendous importance with reference to sustainability. The valorization of marine biomass produces value added compounds containing not only C, H, O but also renewable N atom in the skeleton which widens the scope for its exploration which may prove to be economically beneficial to the society. Heterogeneous catalytic transformation of marine biomass i.e. N-acetyl glucosamine (NAG) to N-substituted aromatic heterocyclic furan derivatives is reported for the very first time. Cost effective and stable metal oxide catalysts were deployed for the transformation. Catalyst screening study showed that La2O3 was found to be an excellent catalyst for N-acetyl glucosamine (NAG) dehydration which mainly produced 3-acetamidofuran (3AF). Methods The physicochemical properties of the metal oxide catalyst were investigated by various techniques such as XRD, FTIR, MeOH-FTIR, TPD, SEM, N-2 sorption studies and HR-TEM analysis for structure activity relationship. Results The effect of various reaction parameters such as catalyst concentration, reaction temperature, reaction time and solvent effect on dehydration of N-acetyl glucosamine has been studied in detail for higher yields. The results revealed that the presence of weak basic sites which are Bronsted in nature and nano pores present on the surface were responsible for improved dehydration of the chitin biomass to selectively yield 3-acetamidofuran (3AF). La2O3 catalyst showed optimum 50% 3AF yield from N-acetyl glucosamine at 180 degrees C in 3 h. Conclusion Efficacious exploitation of marine biomass to value added chemicals using heterogeneous catalysts can be extensively exploited. Separation of N-substituted heterocyclic aromatics is the most innovative aspect of the current study. Thus, utilization of heterogeneous catalyst and renewable biomass as a raw material indicates a transition towards more sustainable and greener approach.{GRAPHICAL ABSTRACT
Keywords: 3-acetamido-5-acetylfuran; 3-acetamidofuran; dehydration; heterogeneous catalysis; Lanthanum oxide; N-acetyl-D-glucosamine; renewable feedstock

Imine oxidation catalyzed by zinc hydroxyapatite: kinetic studies - Vishwakarma, Rakhi; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (ChemistrySelect, 2023)
The synthesis of N,N-diphenylformamide from N-benzylideneaniline and urea hydrogen peroxide is investigated using a zinc hydroxyapatite (ZnHAP) catalyst. It was found that the catalyst resulted in the highest activity of 91 % conversion and 40 % selectivity at 130 degrees C in 2 h. A kinetic model was validated by Langmuir-Hinshelwood-Hougen-Watson (LHHW) at different temperatures and the absence of mass transfer resistance was proved by the Weisz Prater criterion. Effect of different catalysts, catalyst loading, temperature, mole-ratio, and speed of stirring was studied. The as-synthesized catalyst is characterized by FTIR, BET nitrogen adsorption-desorption, TEM, EDX, TPD-NH3, XPS, ICP-MS and XRD. ZnHAP catalyst was found to be stable up to three recycles with no loss in activity.
Keywords: heterogeneous catalysis; hydroxyapatite; imines; Oxidation; Reaction kinetics

Tunable, amine-functionalized porous silica catalyst for CO2 transformation into cyclic organic carbonates at atmospheric pressure - Gorai, Twinkle; Thanasekar, Chandragopal; Kumar, Pawan; Babu, Athira; Kurungot, Sreekumar; Vinod, C. P. (Chemistry-A European Journal, 2025)
A silica catalyst with characteristic features of broad pore size distribution, large pore width and tunable basic sites was synthesized by a one-step green co-condensation synthesis method analogous to SBA-15 synthesis. The surface chemical features of the above catalyst were explored by XPS, N-2 and CO2 adsorption and desorption experiments. The catalyst showed 90% conversion of styrene oxide (SO) with nearly complete selectivity toward styrene carbonate (SC) in 7 hours under a solvent-free condition at a temperature of 120 degrees C with the aid of co-catalyst tetrabutylammonium bromide (TBAB). Moreover, the catalyst demonstrates versatility with various epoxide substrates, providing valuable insights into the cycloaddition reaction under ambient pressure conditions involving carbon dioxide. The mechanistic details of the catalytic conversion were investigated by the in-situ DRIFT studies and reported here.
Keywords: CO2 fixation; cyclic organic carbonates; heterogeneous catalysis; in-situ FTIR

Upgradation of biomass-derived furfural by nanostructured layered double hydroxides: Influence of stirring rate on structural features of materials - Bhagat, Shailesh K.; Nagpure, Atul S.; Lanjewar, Mamata R.; Gode, Nilesh G.; Deshmukh, Ganpat D.; Saini, Ajay (Inorganic Chemistry Communications, 2025)
The proficient conversion of biomass-derived compounds into the high-quality platform chemicals and bio-fuels is enormously imperative to decrease dependence on fossil feedstock. Furfural is a significant bio-based chemical which can be efficiently converted to valuable 4-(2-furyl)-3-buten-2-one (FAc) via aldol condensation. In this work, we have developed prominent layered double hydroxides (LDHs) catalysts for mild aldol condensation of furfural and acetone to acquired high performance with admirable FAc selectivity. Various nanostructured Mg-Al LDHs were synthesized through co-precipitation procedure under different stirring rate conditions. The structural, morphological and optical attributes of materials as well as recyclability aspect and structure-activity relationship was examined by characterizing the fresh and spent catalysts via numerous techniques (XRD, N2 sorption, DLS, CO2-TPD, NH3-TPD, FT-IR, UV-Visible spectroscopy, TGA, SEM, TEM, ICP-OES, 27Al NMR spectroscopy, XPS, Raman spectroscopy, etc). Several reaction parameters were also optimized. Among the catalysts tested, LDH-1200 catalyst exhibits outstanding performance by delivering 100% furfural conversion with 99% FAc selectivity. Moreover, catalyst illustrates excellent recyclability and stability. The mechanistic insight for aldol condensation was also investigated by monitoring the intermediates at different stages and intervals during the course of the reaction. This study confirms that stirring rate has significant influence on physico-chemical attributes of materials and the amount of weak basic sites plays imperative role in catalytic performance.
Keywords: Aldol condensation; Biomass-derived compounds; Flower-shaped nanocrystals; heterogeneous catalysis; Nanostructured mesoporous LDH

Chirality transfer from covalent organic framework nanotubes to covalent organic framework films via chirality induction crystallization - Bag, Saikat; Chatterjee, Debasmita; Mahapatra, Rohan; Sasmal, Himadri Sekhar; Khatua, Arindam; Giri, Madhurima; Paul, Satyadip; Shelke, Ankita; Almasoud, Najla; Alomar, Taghrid S.; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam; et al. (Advanced Materials, 2026)
We report the synthesis of homochiral crystalline covalent organic framework (COF) films that combine rigidity and porosity, offering significant promise for heterogeneous asymmetric catalysis. We prepared enantiopure COF films from achiral diamine and trialdehyde precursors using a chiral induction crystallization strategy. A Schiff-base reaction, catalyzed by a chiral acid, namely (R)- and (S)-camphorsulfonic acids (CSA) generated a beta-ketoenamine backbone with induced chirality. (R)- and (S)-camphorsulfonic acids direct the diamine-trialdehyde condensation and induce chirality during the nucleation of COF nanotubes, enabling their periodic arrangement and the formation of homochiral thin films. We successfully synthesized six distinct COF films with three different backbone functionalities: R-, S-TpAzo; R-, S-TpDPP; and R-, S-TpBDMe2, using the two enantiomers of the chiral camphorsulfonic acids. All films displayed strong circular dichroism signals and pronounced Cotton effects, confirming their enhanced enantiopurity. Both R- and S-TpAzo films exhibited the highest crystallinity, long-range order, and permanent porosity, making them particularly well-suited for catalytic applications. To demonstrate their utility, we encapsulated a bioinspired catalyst, (Et4N)2[FeIII(Cl)bTAML], within the chiral channels of the R- and S-TpAzo films. The resulting composite created a robust heterogeneous catalytic platform for the asymmetric epoxidation of alkenes, achieving excellent activity and enantioselectivity under ambient conditions.
Keywords: chiral induction; covalent organic framework nanotube; covalent organic framework thin film; heterogeneous catalysis

Effect of sulfonation density on acid strength in ion exchange resins: Insights from solid-state NMR and density functional theory - Tumulu, Goutam Narayan; Datar, Sarvesh; Shelke, Ankita; Swain, Gitanjali; Ajithkumar, T. G.; Thirumalaiswamy, Raja; Mohan, Ojus; Mahajani, Sanjay M. (Molecular Catalysis, 2026)
Ion-exchange (IE) resins are widely used as solid acid catalysts; however, their surface acidity remains poorly characterized because their limited thermal stability precludes conventional NH3-based acidity measurements. Moreover, acid-site accessibility in IE resins is strongly governed by solvent- or reactant-induced swelling. Here, we investigate the surface acidity of commercial Amberlyst and Indion IE resins using & sup3;& sup1;P MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance), employing TMPO as a molecular probe dispersed on the resin with moderately swelling dichloromethane, thereby capturing the swollen-state acidity relevant for predicting catalytic activity. The deconvolution of the P-31 MAS NMR spectra reveals three distinct acid-strength zones arising from inhomogeneous sulfonation of the polymer matrix. The overall acidity, quantified by the area-weighted average P-31 chemical shift (delta), increases monotonically with sulfonation density. Notably, only resins containing acid sites stronger than similar to 80 ppm exhibited measurable catalytic activity in alpha-pinene isomerization, establishing a direct correlation between acidity and activity. Density functional theory (DFT) calculations on representative resin models, supported by electron-density analyses, attribute the enhancement of acid strength at higher sulfonation densities to cooperative hydrogen-bonding networks among neighboring sulfonic acid groups. Together, these findings establish P-31 MAS NMR-derived surface acidity as a catalytically relevant descriptor for the rational selection of IE resins in liquid phase acid-catalyzed chemistries.
Keywords: Acid strength; Density functional theory; heterogeneous catalysis; Ion-exchange resins; Solid acids; Solid-state NMR